Peculiarities of migration processes in Ukraine - Толкачова, Ірина Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
After disintegration of the USSR there were created fifteen sovereign states on post-Soviet space. Therefore after proclamation of the independence of Ukraine, scales of migratory processes became significant, what caused spread of massive flows of refugees, repatriates, seekers of asylum etc. Contemporary migratory tendencies make a considerable influence on formation of national politics. Thus, under the conditions of globalization the main tendency in international relationships became migration of labour force. It is caused by different reasons, which become widely-spread both in Ukraine and in the world. Significant growth of intensity of international migration of labour resources on the whole territory of our state makes a great influence on its economic and social development. This causes the necessity to make a profound research of migratory processes in Ukraine. Every person and citizen has a right for freedom of movement. Given right is a basis of migratory law. External migration from Ukraine increased significantly from the moment of proclamation of independence of our state. Among its main reasons are considerable reduction of the level and quality of life of population at the beginning of 1990s, appearance of massive unemployment and herewith simplification of the procedure of exit abroad and change of the place of residence, which became a consequence of democratization of society. At present a big quantity of the citizens of Ukraine works abroad, what is first of all connected with the following important problems in Ukraine: absence of available market of housing, real possibilities of employment, high level of social protection, what leads to growth of unemployment, ineffective politics of employment. Ukrainians often move abroad primarily because of low profits, condition of quality of life, absence of employment. The main for today is provision of free movement for everyone, who is legally on the territory of Ukraine, and promotion to follow of other rights and freedoms of person and citizen.